Characterization of Biodegradable Composites from Polypropylene, Polypropylene Grafted Maleic Anhydride, and Durian Seed Starch - Nasution, Darwin Yunus; Fitri, Rizka Meilia; Siregar, Amir Hamzah (Talenta Publisher, 2022)
The characterization of biodegradable composite from durian seed starch that is mixed polypropylene, and polypropylene grafted maleic anhydride has been done. The stages of this preparation were, the first had prepared durian seed starch, the second had the process of grafting maleic anhydride into polypropylene and the third had made of composite with the composition of PP:PP-g-MA: DSS (7:0.5:0.2); (7:0.5:0.3); (7:0.5:0.4); (7:0.5:0.5); (7:0.5:0.6) (w/w). The biodegradable composites obtained were characterized by tensile strength, surface morphology analysis by SEM, differential thermal analysis (DTA), analysis in nature with the ability to decompose biodegradable test, and functional groups analysis by FTIR spectroscopy. The results showed that the biodegradable composites have the best properties in the ratio of PP:PP-g-MA: DSS was (7:0.5:0.5) (w/w) with the test results of tensile stress is 12.556 N/m2, and the elongation is 8.600%, the images on a few flat surfaces and improved homogeneity, temperature change, and strong group interactions as well as having good biodegradable properties.